Depth sensitive Raman spectroscopy for skin wounds in rodents - Su, Joshua Weiming (2020)
Raman spectroscopy has demonstrated its great potential in skin wound assessment. Given that biochemical changes in skin wound healing is a layer dependent process, depth sensitive Raman spectroscopy could enhance the power of Raman spectroscopy in this application. Considering the critical importance of rodent studies in the field of skin wound assessment, it is necessary to develop and validate a system that can perform depth sensitive measurements in rat skin with a proper target depth range. In this manuscript, we report the design, optimization and evaluation of a new snapshot depth-sensitive Raman instrument for rat skin measurements. The optical design and optimization process are presented first. The depth sensitive measurement performance is characterized on ex vivo rat skin samples with wounds. Raman signal emitted by the ex vivo rat skin from different target depths were simultaneously acquired. The feasibility of using the measured Raman spectra to differentiate between the wound edge and healthy skin was validated using PLS-LDA with leave-one-out. The accuracy of the classification improves monotonically as more data from new depths are used, which implies that each depth offers additional information useful for classification. This instrument demonstrates the ability to perform snapshot depth sensitive Raman measurements from rat skin, which paves the way towards in vivo preclinical studies of rat skin wounds.